Students’ Barriers in Writing Thesis Proposal: Psychological Factors - Rahmianti Devi Puspita Shinta; Andi Rahmawati syarif; Muflihun; Masnawati (International Journal of Research in Education, 2025)
For undergraduate students, writing a thesis is an essential academic requirement since it offers a chance to combine theoretical knowledge with useful research techniques. However, the process of writing a thesis can be extremely difficult in developing nations like Indonesia, mostly because of psychological hurdles that have not received enough attention in local studies. The purpose of this study is to look at the psychological obstacles that Universitas Muhammadiyah Kendari students enrolled in the English Language Education Program encounter when drafting their thesis proposals. Data were gathered from four final-year students using semi-structured interviews and open-ended questionnaires using a descriptive qualitative methodology. Three primary themes emerged from the thematic analysis: challenges in starting and maintaining a writing career, effects on one's physical and mental well-being while writing, and methods and social support employed to get beyond these hurdles. It was discovered that psychological barriers including procrastination, anxiety, insecurity, and fear of failing have a detrimental impact on students' wellbeing and considerably slow down the writing process. Support from peers, family, and supervisors as well as individual coping mechanisms were essential in assisting students in handling the demands of their studies. Higher education institutions should offer holistic guidance approaches and a supportive learning environment to improve students' mental health and thesis completion, according to the study's findings, which also show that emotional and psychological preparedness is just as important for academic success as intellectual proficiency.